Millisecond timescale fluctuations in dihydrofolate reductase are exquisitely sensitive to the bound ligands - Boehr, David D. (National Academy of Sciences, 2010)
Enzyme catalysis can be described as progress over a multi-dimensional energy landscape where ensembles of interconverting conformational substates channel the enzyme through its catalytic cycle. We applied NMR relaxation dispersion to investigate the role of bound ligands in modulating the dynamics and energy landscape of Escherichia coli dihydrofolate reductase to obtain insights into the mechanism by which the enzyme efficiently samples functional conformations as it traverses its reaction pathway. Although the structural differences between the occluded substrate binary complexes and product ternary complexes are very small, there are substantial differences in protein dynamics. Backbone fluctuations on the μs-ms timescale in the cofactor binding cleft are similar for the substrate and product binary complexes, but fluctuations on this timescale in the active site loops are observed only for complexes with substrate or substrate analog and are not observed for the binary product complex. The dynamics in the substrate and product binary complexes are governed by quite different kinetic and thermodynamic parameters. Analogous dynamic differences in the E:THF:NADPH and E:THF:NADP(+) product ternary complexes are difficult to rationalize from ground-state structures. For both of these complexes, the nicotinamide ring resides outside the active site pocket in the ground state. However, they differ in the structure, energetics, and dynamics of accessible higher energy substates where the nicotinamide ring transiently occupies the active site. Overall, our results suggest that dynamics in dihydrofolate reductase are exquisitely “tuned” for every intermediate in the catalytic cycle; structural fluctuations efficiently channel the enzyme through functionally relevant conformational space.